VD_FINDINFO HC / 2018 / 813 vom 4. September 2018 - VD Tribunal cantonal (2018)
RESTITUTION DU DÉLAI, FAUTE LÉGÈRE, AVANCE DE FRAIS | 101 al. 1 CPC (CH), 101 al. 3 CPC (CH), 147 al. 1 CPC (CH), 148 CPC (CH)